2018
DOI: 10.1111/iju.13801
|View full text |Cite
|
Sign up to set email alerts
|

Role of systemic inflammatory response markers in urological malignancy

Abstract: The systemic inflammatory response is associated with survival in patients with a variety of cancers. This inflammatory response is measured in the peripheral blood, and can be monitored using two categories of indices: concentration of specific serum proteins (albumin, C‐reactive protein) and differential blood cell count (neutrophils, lymphocytes and platelets). Furthermore, combinations of these indices, such as the Glasgow Prognostic Score, which consists of the serum C‐reactive protein and albumin level; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 164 publications
(361 reference statements)
0
61
1
1
Order By: Relevance
“…PNI is a combination of serum albumin and peripheral blood lymphocyte count. High values of PNI are associated with a good prognosis in cancer patients [84]. Studies evaluating the prognostic value of PNI in patients with RCC are few but confirm these results [129][130][131][132][133][134][135].…”
Section: Inflammation As Prognostic Factormentioning
confidence: 88%
See 1 more Smart Citation
“…PNI is a combination of serum albumin and peripheral blood lymphocyte count. High values of PNI are associated with a good prognosis in cancer patients [84]. Studies evaluating the prognostic value of PNI in patients with RCC are few but confirm these results [129][130][131][132][133][134][135].…”
Section: Inflammation As Prognostic Factormentioning
confidence: 88%
“…These cytokines are produced in various cells, including inflammatory cells and cancer cells. Thus, serum CRP concentration might be elevated due to hepatic stimulation by cancer-cell-derived inflammatory cytokines [84].…”
Section: Inflammation As Prognostic Factormentioning
confidence: 99%
“…To make right treatment decisions for the right patient at right timing, a detailed prognosis estimation is needed. Recent studies have shown that elevated tumor markers, such as LDH and ALP, and some in ammatory markers are poor prognostic factors for CRPC [6]. Zhao et al developed a prognostic nomogram for CRPC among Chinese patients using a 449-patient cohort [18].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous clinical prognostic or predictive factors have been identi ed based on clinical trials and retrospective univariate or multivariate analysis, including performance status, appearing symptoms, and paraneoplastic syndromes [6]. Besides, laboratory values are also used for prognosis, such as serum protein, corrected calcium, erythrocyte sedimentation rate, and neutrophil to lymphocyte ratio [7,8].…”
Section: Introductionmentioning
confidence: 99%